SOCIAL MEDIA USE ON MENTAL HEALTH AMONG ADOLESCENTS - Hassan, Mohd Sufiean; Mohd Din, Nur Ilyia Iwana; Zainal, Zairul Anis Azureen; Hamzah, Nur Syazliana; Mohd Jaini, Siti Nur Nadhirah; Azli, Azreen Darrin; Yusuf, Norli (Jurnal 'Ulwan, 2023)
Social media platforms (e.g., Facebook, Instagram, or Twitter) have become increasingly popular among adolescents. This systematic review examines the research on the association between active social media usage and common mental health outcomes (anxiety, depression, and fear of missing out) in adolescents. Therefore, using the world's biggest abstract and citation database for peer-reviewed literature, Scopus was reviewed for empirical studies that looked into this connection among adolescents. Empirical research methodology has included synthesis of local and international experience, comparative evaluation, a scientific experimentation gained through observation, and qualitative assessment of the research materials. As result, a significant association between social media and negative mental health were found. Overall, the link between social media and emotional disorder (anxiety, depression and fear of missing out) has given the public health implications at risk and demands more inquiry to indicate the intensity and invariance of the outcomes.